1990
DOI: 10.1126/science.2105528
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Transcription Factors that Bind the Immunoglobulin Enhancer μE5/κE2 Motif

Abstract: Activity of the immunoglobulin heavy and kappa light chain gene enhancers depends on a complex interplay of ubiquitous and developmentally regulated proteins. Two complementary DNAs were isolated that encode proteins, denoted ITF-1 and ITF-2, that are expressed in a variety of cell types and bind the microE5/kappa 2 motif found in both heavy and kappa light chain enhancers. The complementary DNAs are the products of distinct genes, yet both ITF-1 and ITF-2 are structurally and functionally similar. The two pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
330
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(340 citation statements)
references
References 33 publications
9
330
0
1
Order By: Relevance
“…Functional studies indicate a positive regulatory role for E2A-HLF in gene expression, mediated through two separate domains (AD1 and AD2) in the E2A fusion element that act as potent trans-activators of gene expression in several contexts (12,13,(29)(30)(31). By contrast, NFIL3͞E4BP4 can function as either a trans-repressor or trans-activator of transcription in different cell types and promoter contexts (18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Functional studies indicate a positive regulatory role for E2A-HLF in gene expression, mediated through two separate domains (AD1 and AD2) in the E2A fusion element that act as potent trans-activators of gene expression in several contexts (12,13,(29)(30)(31). By contrast, NFIL3͞E4BP4 can function as either a trans-repressor or trans-activator of transcription in different cell types and promoter contexts (18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Members of the E2A family include E2-2, HEB and the products of the E2A gene E47 and E12 (Murre et al, 1989;Henthorn et al, 1990;Hu et al, 1992). Tal-1/E2A heterodimers preferentially recognize the E-box consensus sequence CAGATG (Hsu et al, 1994a) and exhibit transcriptional transactivation activity (Hsu et al, 1994c).…”
Section: Introductionmentioning
confidence: 99%
“…These clones were plaque purified, and the nucleotide sequence of a portion of each cDNA was determined (23). Analyses of these sequences revealed that one cDNA encoded the regulatory factor, E12 (26) and the other cDNA encoded the transcription factor, USF2 (14,25). Both E12 and USF2 have been shown to bind to E-box elements and to regulate the expression of a number of genes.…”
Section: Resultsmentioning
confidence: 99%
“…The human USF2a and USF2b expression cDNAs (25) and the mouse wild-type USF2a, mutant USF2a⌬N, and mutant TDUSF2a⌬B expression cDNAs (9) were generous gifts from Dr. Raymondjean and Dr. Sawadogo, respectively. The E12 expression vector was generously provided by Dr. Kadesch (26).…”
Section: Materials-mentioning
confidence: 99%